Association of Fibroblast Growth Factor-23 Levels and Angiotensin-Converting Enzyme Inhibition in Chronic Systolic Heart Failure - Wohlfahrt, Peter; Melenovsky, Vojtech; Kotrc, Martin; Benes, Jan; Jabor, Antonin; Franekova, Janka; Lemaire, Sophia; Kautzner, Josef; Jarolim, Petr (JACC. Heart failure, 2015)
OBJECTIVES: The aim of this study was to evaluate the association of fibroblast growth factor (FGF)-23 with clinical and laboratory findings, the prognostic value of FGF-23, and the relationship between angiotensin-converting enzyme inhibitor (ACEi) therapy, FGF-23 levels, and outcomes in patients with chronic systolic heart failure (HF). BACKGROUND: FGF-23 is a bone-derived hormone regulating mineral metabolism. Higher FGF-23 levels are associated with an increased risk of cardiovascular mortality or HF development. Mechanisms leading to increased FGF-23 and its prognostic value have not been thoroughly studied in HF. METHODS: FGF-23 was measured in 369 patients (mean age 59 ± 11 years, 84% male) with systolic HF. Patients were followed for adverse events (e.g., death, urgent heart transplantation, ventricular assist device implantation). RESULTS: Tricuspid regurgitation severity, chronic kidney disease (CKD), alkaline phosphatase concentrations, inferior vena cava dilation, and absence of ACEi therapy were independently associated with FGF-23. FGF-23 was independently associated with outcomes in patients without CKD (hazard ratio [HR]: 1.43, 95% confidence interval [CI]: 1.14 to 1.78), but not in CKD patients (HR: 1.12, 95% CI: 0.87 to 1.45). In patients without CKD and with FGF-23 in the highest tertile, ACEi therapy was associated with a lower risk of adverse events (HR: 0.42, 95% CI: 0.21 to 0.81), whereas no association was seen in the remaining patients (HR: 1.18, 95% CI: 0.52 to 2.70). CONCLUSIONS: In systolic HF, elevated FGF-23 is an independent predictor of adverse events, particularly in patients with preserved renal function. The association of FGF-23 with adverse events likely reflects early alterations of renal hemodynamics and renin-angiotensin system activation. Increased FGF-23 may identify a subset of HF patients benefiting from ACEi therapy.
Keywords: Male; Biomarkers; Absorptiometry, Photon; Kaplanův-Meierův odhad; heart failure; Treatment Outcome; systolické srdeční selhání; lidé středního věku; Fibroblast Growth Factor-23; fibroblastové růstové faktory; retrospektivní studie; stupeň závažnosti nemoci; Heart Failure, Systolic; Cohort Studies; prediktivní hodnota testů; fibroblast growth factor-23; dopplerovská echokardiografie; Humans; chronická nemoc; Angiotensin-Converting Enzyme Inhibitors; Kidney Function Tests; Kaplan-Meier Estimate; Middle Aged; Risk Assessment; Survival Analysis; senioři; biologické markery; prognóza; hodnocení rizik; mužské pohlaví; Prognosis; Female; adverse events; Predictive Value of Tests; kohortové studie; chronické selhání ledvin; Echocardiography, Doppler; Aged; vyšetření funkce ledvin; ženské pohlaví; Retrospective Studies; angiotensin-converting enzyme inhibitor; Severity of Illness Index; outcome; fibroblastový růstový faktor 23; Chronic Disease; výsledek terapie; analýza přežití; multivariační analýza; inhibitory ACE; lidé; Fibroblast Growth Factors; Multivariate Analysis; Kidney Failure, Chronic; absorpční fotometrie